ประสิทธิภาพการกันความร้อนของแผงอลูมิเนียมฉลุลาย - ยงยุทธ อิ่มสงวน (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The objective of this research was to study the performance of perforated aluminum shading on reducing indoor heat gain by comparing the shading screens that were different in perforation percentage. In addition, the research was conducted to study the relationship between shading pattern and heat transfer. The other purpose of this study was to determine the proper choice of aluminum shading pattern by considering the building type. Heat transfer coefficient (U-value) and Shading coefficient (SC) were calculated to find out the best solution in this stage. The thermal simulation was carried out by using four different perforation percentages that were 20%, 35%, 50% and 65% in three different colors, white, gray and black. A row-house building was used as a reference building. For the first stage of the experiment, the temperature data of the test box was measured and recorded in order to calculate U-value and Shading coefficient (SC) with mathematical method. U-value and SC from the test box were used as the variables in computer simulation of the reference building. The results of cooling energy consumption in the simulation were compared to establish guidelines for building energy retrofit. The results demonstrated that the building screen with 20% perforation percentage performed the best for reducing heat gain in building, followed by the building screen with 35%, 50%, 65% and non-shading device, respectively. The residential building using white aluminum shading with 20% perforation showed the highest percentage of energy saving that was 20.65%. However, the result performed most effectively on the South. This offered a payback period of 22 years 10 months and 24 days